2013
DOI: 10.3846/13923730.2013.801896
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Secondary Reinforcements in Reinforced Concrete Corbels

Abstract: The study is concerned with normal-strength concrete corbels. 30 such corbels were studied by finite element modelling and the variables considered include ratios of primary and secondary reinforcement, type of applied loading, vertical or horizontal. Finite element modelling with a software package LUSAS was used to analyse four series of corbels namely PV series (primary reinforcement with vertical loading), SV series (secondary reinforcement with vertical loading), PH series (primary reinforcement with hori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…They indicated that increasing percentage of primary reinforcement steel can improve the ultimate load of a corbel. Also, load-carrying capacity of a corbel can be increased by adding secondary reinforcement up to 0.3 % [16]. In 2015, Ivanova and Assih investigated behavior of RC short corbels retrofitted by bonding composite carbon fiber fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that increasing percentage of primary reinforcement steel can improve the ultimate load of a corbel. Also, load-carrying capacity of a corbel can be increased by adding secondary reinforcement up to 0.3 % [16]. In 2015, Ivanova and Assih investigated behavior of RC short corbels retrofitted by bonding composite carbon fiber fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…Internal primary and secondary (closed stirrups) reinforcements are incorporated into the design of the corbels to prevent brittle failure under excessive horizontal and vertical loads. Several studies have been performed, both experimental and analytical, on the main parameters governing the structural behaviour of corbels, such as reinforcement ratio, shape and geometry, and concrete strength [2][3][4]. When the ratio of primary reinforcement is low, it enables the members to achieve higher ductility because of yielding of reinforcement prior to the concrete.…”
Section: Introductionmentioning
confidence: 99%